Directions for the formation of «City Intelligent models» using artificial intelligence for the post-war reconstruction of historical buildings - Chashyn, Dmytro; Khurudzhi, Yelyzaveta; Daukšys, Mindaugas (Budownictwo i Architektura / Civil and Architectural Engineering, 2024)
Addressing the limitations of current digital simulations for historical buildings, this paper suggests a specific technical task for the development of a simulation analysis platform based on City Intelligent Modelling (CIM). The objective is to establish a systematic approach for digitally maintaining and managing historical dwellings. The technique presented in this paper focuses on constructing sophisticated parametric models that offer numerous modelling benefits, allowing for convenient updates to the Historic Building Information Modelling (HBIM). The text discusses various applications and integrations of Building Information Modelling (BIM) in urban planning, construction projects, and historic building renovations. CIM is presented as a comprehensive digital platform that visually represents cities, aiding urban planners in decision-making for sustainable development. The text delves into the use of advanced analytical tools within CIM for diverse data analysis, predictive modelling, and simulation to forecast trends. The focus shifts to the evolution of BIM, progressing from 3D to 5D models, influencing construction project management and cost estimation. The integration of BIM in historic building projects is explored, emphasising the challenges and proposing innovative solutions using HBIM. The paper also introduces the concept of Infrastructural Building Information Modelling (InfraBIM) in construction management, incorporating Virtual and Augmented Reality for enhanced visualisation.